O paradigma frankfurteano: uma alternativa para a psicologia organizacional - Moura, Wilson (1987)
This thesis aims to propose a thearetical model of performance for the Organizational Psychology based on the following fundamentals: the dialectic sight of the individual/organization interaction provided by the revaluation of the concept of partial inclusion in Floyd Allport's the memory's recovery of past events that have influenced the dynamies of organizational interaction; Juergen Habermas theory of communicative competence and Pichon-Riviére’s method of operative groups. The way followed to achieve such aim was based Kuhn's presuppositions by forming an initial hypothesis that problems faced the organizational psychology are originated from points of bliefs that guide the production of knowledge in the area. In order to prove such statement, an analysis of several currents responsible for the main theoretical contributions in this field was estabilished and a such currents were classified in the following paradigmas: bureaucratic, open system, human relations, humanist and of the contingency, simultaneously the epistemic hidrances presented by the respective paradigms were pointed out. Among the contributions of theorists pertaining to the philosophic movement – knoen as Frankfurt School – we searched those considered the most significant for understanding the phenomena that constitute the aim of the organizational Psychology. Such contributions formed, thus, the basis for the proposed model. As a consequence of having adopted the Frankfurt School’s paradigm we came to a reorientation in the field and aim of the organizational Psychology and at the same time it was possible to see clearly a link with field of performance of Industrial Psychology a link with fields of performance of industrial Psychology and of Institutional Psychology.